2020
DOI: 10.1523/jneurosci.2368-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Capacity Limits in Perception: A Cellular Metabolism Account

Abstract: Limits on perceptual capacity result in various phenomena of inattentional blindness. Here we propose a neurophysiological account attributing these perceptual capacity limits directly to limits on cerebral cellular metabolism. We hypothesized that overall cerebral energy supply remains constant, regardless of overall mental processing demands; therefore, an attention mechanism is required to regulate limited cellular metabolism levels in line with attended task demands. Increased perceptual load in a task (im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…This might indicate distinct spatial localisation of the cytochrome response in comparison to the haemodynamics. Studies have demonstrated that task-related increases in oxidative metabolism and energy demand were smaller (approximately 15%) in comparison to the increase in CBF (approximately 60%) (Lin et al, 2010;Bruckmaier et al, 2020), which could potentially explain the fewer number of channels activated for oxCCO. Indeed, previous studies have suggested that oxygen consumption is more spatially specific in comparison to changes in cerebral blood flow (Malonek and Grinvald, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…This might indicate distinct spatial localisation of the cytochrome response in comparison to the haemodynamics. Studies have demonstrated that task-related increases in oxidative metabolism and energy demand were smaller (approximately 15%) in comparison to the increase in CBF (approximately 60%) (Lin et al, 2010;Bruckmaier et al, 2020), which could potentially explain the fewer number of channels activated for oxCCO. Indeed, previous studies have suggested that oxygen consumption is more spatially specific in comparison to changes in cerebral blood flow (Malonek and Grinvald, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…BOLD responses are typically negatively correlated with alpha band power [39][40][41] . Similarly, using spectroscopy, Bruckmaier et al 14 recently showed increased cellular metabolism for attended target and a reduction for unattended stimuli with increased perceptual load. The current results thus provide evidence that the previously observed resource reduction for the distractor due to a target load increase is implemented by an increase in alpha band power.…”
Section: Perceptual Load Results In Increased Distractor Suppression mentioning
confidence: 89%
“…As alpha band oscillations have been shown to reflect functional inhibition 12,13 , the primary role of alpha oscillations is thought to be the suppression of the processing pathway of the irrelevant items as well as engaging the attended pathway by a decrease in alpha power. Perceptual load theory predicts a reduction of resources for distractors with increased target processing load 14 . However, it remains unclear how the theory relates to modulations in the alpha band.…”
Section: Introductionmentioning
confidence: 99%
“…Even a brief interval above average energy levels in a limited cerebral region needs to be balanced out by reductions in metabolism elsewhere (Clarke and Sokoloff, 1999 ). Lennie ( 2003 ) writes: “Even with only a few percent of neurons concurrently active in any local region, the metabolic burden would be unsustainable over all of cortex.” A consequence of this is that, if attention is devoted to a visual discrimination task, processing capacity is lower for other unattended processes (Bruckmaier et al, 2020 ). Since inattentive visual processes constitute by far the largest part of total perceptual content (see below), energy considerations make it unlikely that inattentive perception is mediated by current neuronal activity.…”
Section: Supporting Evidencementioning
confidence: 99%